Penerapan Model Kooperatif Tipe Jigsaw Dalam Pembelajaran PPKn Untuk Meningkatkan Hasil Belajar Pada Siswa Kelas X diSekolah SMAN 3 Kota Gorontalo - Moh Mufarid J. Hasani; Sukarman Kamuli; Roni Lukum (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2026)
This study was motivated by the low level of student participation and learning outcomes in Civic Education at SMA Negeri 3 Gorontalo, which was still dominated by conventional teaching approaches. The research aimed to analyze the implementation of the Jigsaw cooperative learning model and examine its effectiveness in improving students’ interest and academic achievement. The method employed was Classroom Action Research conducted in two cycles, consisting of planning, implementation, observation, and reflection stages. Data were collected through observation, questionnaires, and learning achievement tests, then analyzed quantitatively using percentages and mean scores. The findings revealed a significant improvement in students’ average scores and learning mastery in the second cycle, exceeding the predetermined criteria. It can be concluded that the Jigsaw model effectively enhances student participation and learning outcomes in a more active, collaborative, and meaningful learning environment.